1990
DOI: 10.1093/oxfordjournals.aob.a088084
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Function for Crop Growth Based on Light Interception and Leaf Area Expansion

Abstract: The Richards function is often inappropriate to describe growth for crop stands, in which dry matter characteristically increases at an almost constant rate during the main growth stage. An alternative function with a more physiological basis is developed by assuming that, when light is limiting, growth rate is proportional to intercepted radiation and therefore to an exponential function of leaf area. As the function describes the transition from exponential to linear growth, the name expolinear growth equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(123 citation statements)
references
References 8 publications
3
115
0
5
Order By: Relevance
“…Hence, we developed the present study to focus on light interception and utilization by soybean plants because both are key constituents for dry matter accumulation. Ball et al (2000) argued that having a short duration before the full canopy cover is achieved (>90% light interception) may increase yield because it shortens the time required after emergence to begin linear biomass accumulation, which Goudriaan and Monteith (1990) is considered to be lost time. Lee et al (2008) showed that achieving complete ground cover by the R1 [stage in the classification of Fehr and Caviness (1977)] or shortly thereafter is required to achieve maximum yield.…”
Section: Experimental Site Cultivars and Field Managementmentioning
confidence: 99%
“…Hence, we developed the present study to focus on light interception and utilization by soybean plants because both are key constituents for dry matter accumulation. Ball et al (2000) argued that having a short duration before the full canopy cover is achieved (>90% light interception) may increase yield because it shortens the time required after emergence to begin linear biomass accumulation, which Goudriaan and Monteith (1990) is considered to be lost time. Lee et al (2008) showed that achieving complete ground cover by the R1 [stage in the classification of Fehr and Caviness (1977)] or shortly thereafter is required to achieve maximum yield.…”
Section: Experimental Site Cultivars and Field Managementmentioning
confidence: 99%
“…The Goudriaan and Monteith (1990) expo-linear model was adapted for hydrological purposes. The expo-linear model allowed to characterize the RC as two change ratios, the maximum runoff ratio (C) which discriminated the phase associated with the direct flow (linear), and a relative runoff ratio (k) associated to the baseflow (exponential).…”
Section: Methodsmentioning
confidence: 99%
“…The responses of the rate of photosynthesis to variations in environmental factors can be described in terms of the biochemical processes of electron transport and carbon dioxide fixation [27], or carbon dioxide assimilation by leaves and plant canopies [16,28,29], or by dry matter accumulation at the crop level [30,31]. The modelling approaches differ in the way in which this conversion is expressed, and the interactions with other processes that are incorporated into the energy conversion coefficient.…”
Section: Photosynthetic Modelsmentioning
confidence: 99%
“…In spite of the theoretical superiority of the biochemical model and because detailed biochemical and physiological information is lacking for many crop species, empirical leaf and canopy models still provide satisfactory empirical predictions of the relative effects of environmental factors on crop yield or forest production [29,31,34,35]. Where variations in plant condition or soil or atmospheric water deficits [16,17,20] may influence carbon dioxide assimilation and dry matter production, it is necessary to extend the model beyond the effects of the factors considered in Table 1.…”
Section: Photosynthetic Modelsmentioning
confidence: 99%